Pengembangan E-Booklet Pada Konsep Sistem Imun Untuk Meningkatkan Hasil Belajar Peserta Didik : (Development of E-Booklet on Immune System Concepts to Improve Learners' Learning Outcomes) - Lestari, Tiwi; Kaspul , Kaspul; Nurtamara, Luthfiana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The ability of Higher Order Thinking Skills (HOTS) needed by students to analyze immune system concepts was not easy to understood by the students. This research development E-booklet because the results of the questionnaire analysis of the needs of teachers and students expected teaching materials that are simple, with easy-to-understand sentences, and have interesting picture illustrations. The purpose of this research is to describe the suitability, feasibility, readability, and effectiveness of the development E-booklet on the concept of the immune system. This research and development with the 4D model; 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The subjects of this research 3 validators and 12 students of class XII SMAN 1 Alalak. The Define stage resulted in needs analysis, learner analysis, task analysis, concept analysis, and specification of learning objectives. The design stage resulted in the preparation of criterion reference tests, media selection, format selection and E-booklet design. The Develop stage produces data on suitability, feasibility, readability and effectiveness. The results of testing the suitability of the E-booklet indicate that it is very suitable with a score of 4.45, meaning that the E-booklet is in accordance with the aspects of learning objectives, language, format and media. The results of feasibility testing indicate that it is very feasible with a score of 4.48, meaning that the E-booklet is feasible to be used by students. The readability results indicate that it is very good with a score of 4.56, meaning that the E-booklet is easy to read and understood by students. The effectiveness test results obtained a pretest score of 19.81 and a posttest score of 56.96, an increase score of 37.15 after using the E-booklet. The booklet of immune system concepts can be used to guide students in the learning of immune system material to improve learning outcomes, especially the ability to analyse the immune system. Abstrak. Kemampuan Higher Order Thinking Skills (HOTS) perlu dimiliki peserta didik untuk menganalisis materi sistem imun karena dianggap tidak mudah dipahami oleh peserta didik. Penelitian ini mengembangkan E-booklet dikarenakan hasil angket analisis kebutuhan guru dan siswa mengharapkan adanya bahan ajar yang singkat, kalimat yang mudah dipahami dan ada ilustrasi gambar menarik. Tujuan dari penelitian ini yaitu mendeskripsikan kesesuaian, kelayakan, keterbacaan dan keefektifan terhadap hasil pengembangan E-booklet konsep sistem imun. Penelitian dan pengembangan ini menggunakan model 4D yaitu, 1) Define, 2) Design, 3) Develop, dan 4) Disseminate. Subjek dari penelitian ini yaitu 3 validator dan 12 peserta didik kelas XII SMAN 1 Alalak. Tahapan Define didapatkan hasil analisis kebutuhan, analisis peserta didik, analisis tugas, analisis konsep, dan spesifikasi tujuan pembelajaran. Tahap Design didapatkan hasil penyusunan tes acuan kriteria, pemilihan media, pemilihan format dan rancangan E-booklet. Untuk mengetahui kesesuian, kelayakan dan keterbacaan maka data yang awalnya berupa skor diolah menjadi data kualitatif (data interval) dengan skala likert. E-booklet menandakan sangat sesuai dengan skor 4,45, artinya E-booklet sesuai dengan aspek tujuan pembelajaran, bahasa, format dan media. Hasil pengujian kelayakan menandakan sangat layak dengan skor yaitu 4,48, artinya E-booklet layak digunakan oleh peserta didik. Hasil keterbacaan menandakan sangat baik dengan skor yaitu 4,56, artinya E-booklet mudah dibaca dan dipahami oleh peserta didik. Hasil uji keefektifan didapatkan hasil nilai pretest (19,81) dan posttest (56,96) adanya peningkatan nilai setelah penggunaan E-booklet sebesar 37,15. E-booklet konsep sistem imun ini dapat digunakan oleh peserta didik dalam pembelajaran sistem imun untuk meningkatkan hasil belajar, khususnya kemampuan menganalisis terhadap sistem imun.